THE CONTENT OF THE CONCEPTS OF “INNOVATIVE EDUCATIONAL TECHNOLOGIES” AND “EDUCATIONAL INNOVATIONS” - Sharipova Aziza Mustafayevna (International Journal of Innovations in Engineering Research and Technology, 2023)
The article covers methodological recommendations on the content of the concepts of “innovative educational technologies” and “educational innovations” of teachers operating in secondary schools.